Monthly review :
German ed.: Monthly review. Unabhängige sozialistische Zeitschrift (ZO 31656). - Ital.ed.: Monthly review. Ed. italiana (ZK 32651). - Span.ed.: Monthly review. Revista mensual de investigacion politica internacional... (ZO 31657).